Converging Modalities Ground Abstract Categories: The Case of Politics - Farias, Ana Rita; Garrido, Margarida V.; Semin, Gün R. (PLOS ONE, 2013)
Three studies are reported examining the grounding of abstract concepts across two modalities (visual and auditory) and their symbolic representation. A comparison of the outcomes across these studies reveals that the symbolic representation of political concepts and their visual and auditory modalities is convergent. In other words, the spatial relationships between specific instances of the political categories are highly overlapping across the symbolic, visual and auditory modalities. These findings suggest that abstract categories display redundancy across modal and amodal representations, and are multimodal.